2010
DOI: 10.1021/jf904306r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Cooking Methods on Color, Phytochemical Concentration, and Antioxidant Capacity of Raw and Frozen Brassica Vegetables

Abstract: This study evaluated the effect of common cooking practices (i.e., boiling, microwaving, and basket and oven steaming) on the phytochemical content (carotenoids, chlorophylls, glucosinolates, polyphenols, and ascorbic acid), total antioxidant capacity (TAC), and color changes of three generally consumed Brassica vegetables analyzed fresh and frozen. Among cooking procedures, boiling determined an increase of fresh broccoli carotenoids and fresh Brussels sprout polyphenols, whereas a decrease of almost all othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

46
184
4
17

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(251 citation statements)
references
References 37 publications
46
184
4
17
Order By: Relevance
“…In the present study, the most abundant phenolic acid in cauliflower curds was caffeic acid, followed by p-coumaric acid, sinapic acid, gallic acid and ferulic acid (Table 4). These results are in agreement with studies conducted by Pellegrini et al (2010) and Mazzeo et al (2011), but not with the study of Sikora et al (2012). These authors reported p-coumaric acid to be most abundant, followed by sinapic acid, caffeic acid and ferulic acid.…”
Section: Phenolic Compoundssupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, the most abundant phenolic acid in cauliflower curds was caffeic acid, followed by p-coumaric acid, sinapic acid, gallic acid and ferulic acid (Table 4). These results are in agreement with studies conducted by Pellegrini et al (2010) and Mazzeo et al (2011), but not with the study of Sikora et al (2012). These authors reported p-coumaric acid to be most abundant, followed by sinapic acid, caffeic acid and ferulic acid.…”
Section: Phenolic Compoundssupporting
confidence: 88%
“…These data are in agreement with Sikora et al (2012). In the studies conducted by Mazzeo et al (2011) and Pellegrini et al (2010) caffeic acid content was almost 4-fold higher. On the other hand, Ahmed and Ali (2013) found 8-fold lower caffeic acid content.…”
Section: Phenolic Compoundsmentioning
confidence: 85%
“…It has been reported that cooking caused a significant alteration in chemical compositions as well as antioxidant activities of grains and cereals (Pellegrini et al., 2010). Alpha‐amylase and alpha‐glucosidase play crucial role in sudden rise in blood glucose level observed in diabetic patients after taking carbohydrate‐rich foods due to hydrolysis of carbohydrate by these enzymes into simpler monomeric unit (glucose) (Kim, Jeong, Wang, Lee, & Rhee, 2005; Kwon, Vattem, & Shetty, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…before consumption and these processing techniques have effect on the concentration and bioavailability of some vital nutrients and compounds. Previous studies showed that cooking significantly reduced total phenolic contents of some grains (Pellegrini et al., 2010; Towo, Svanberg, & Ndossi, 2003). Having in mind the lack of scientific literatures on the effect of cooking on in vitro GI, α‐amylase, and α‐glucosidase inhibitory properties of grains, therefore, present study was designed to assess the effect of cooking on amylose and amylopectin contents, sugar and starch contents, GI, and antioxidant properties of two rice varieties, as well as their effects on starch hydrolyzing enzymes (α‐amylase and α‐glucosidase).…”
Section: Introductionmentioning
confidence: 99%
“…At present, carrot juice products adopt the traditional way of thermal processing. It is known that thermal processing induces significant changes in chemical composition, affecting the bioaccessibility and the concentration of nutrients and health-promoting compounds such as vitamin C, carotenoids, and polyphenols [1].…”
Section: Introductionmentioning
confidence: 99%